KASURAN DALAM BERAGAM SUDUT PANDANG MERUNUT JEJAK-JEJAK CERITA TIDUR TANPA KASUR DI DUSUN KASURAN - Saifuddin Zuhri Qudsy; Irwan Abdullah; Zuly Qodir (Jurnal Kawistara, 2015)
In this article the authors examine various perspectives or viewpoints that exist in the hamlet of Kasuran on myths about sleeping without a mattress. It is important and often overlooked in a variety of reports in the media. By using Bourdieu perspective, the authors reveal that how the various viewpoints ’fight’ each other to gain social recognition that this myth persist until today. Because of fighting each others in a field named Kasuran the myth is producted and reproducted since hundreds years ago.